BIOCHAR SEKAM PADI SEBAGAI AMELIORAN UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL TERONG ‘YUFITA F1’ - Zulkarnain, Zulkarnain; Rainiyati, Rainiyati; Tarigan, Indah Sri Ulina (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2026)
Eggplant is a very popular fruit vegetable and is in high demand, so the continuity and stability of its production needs to be maintained through various strategic efforts in its cultivation. Therefore, this study aimed to investigate the effect of various doses of rice husk biochar, and to obtain an optimum dose of biochar that could increase the growth and production of eggplants. Field trial was carried out at the facility of Teaching and Research Farm, Faculty of Agriculture, University of Jambi, from May to August 2025. The variables tested were 6 levels of rice husk biochar, namely 2.50 tons·ha-1; 5.50 tons·ha-1; 7.50 tons·ha-1; 10.00 tons·ha-1; 12.50 tons·ha-1 and without biochar as a control. The experiment employed a simple completely randomized design. Each level of biochar consisted of 4 replications, and there were 10 individuals in each replication. The results showed that rice husk biochar significantly affected plant height, time to harvest, weight per individual fruit, total fruit weight per plant and production per hectare. However, biochar application did not affect total number of fruits per plant, fruit diameter and fruit length. In general, this investigation revealed that the application of 7.50 tons·ha-1 of biochar made from rice husk was effective to improve the physical condition of the soil, thereby encouraging optimal eggplant production.